Method Matters: Effect of Purification Technology on Neutrophil Phenotype and Function - Blanter, Marfa; Cambier, Seppe; De Bondt, Mirre; Vanbrabant, Lotte; Pörtner, Noëmie; Abouelasrar Salama, Sara; Metzemaekers, Mieke; Marques, Pedro Elias; Struyf, Sofie; Proost, Paul; Gouwy, Mieke (Frontiers in Immunology, 2022)
Neutrophils are the most abundant leukocytes in human blood and the first cells responding to infection and injury. Due to their limited ex vivo lifespan and the impossibility to cryopreserve or expand them in vitro, neutrophils need to be purified from fresh blood for immediate use in experiments. Because of their sensitivity, neutrophil purification methods may artificially modify the phenotype and functional characteristics of the isolated cells. The aim of this study was to expose the effects of ‘classical’ density-gradient purification versus the more expensive but faster immunomagnetic isolation on neutrophil phenotype and functionality. We found that in the absence of inflammatory stimuli, density-gradient-derived neutrophils showed increased polarization responses as well as enhanced release of reactive oxygen species (ROS), neutrophil extracellular traps (NETs) and granular proteins compared to cells derived from immunomagnetic isolation, which yields mostly quiescent neutrophils. Upon exposure to pro-inflammatory mediators, immunomagnetic isolation-derived neutrophils were significantly more responsive in polarization, ROS production, phagocytosis, NETosis and degranulation assays, in comparison to density-gradient-derived cells. We found no difference in chemotactic response in Multiscreen and under-agarose migration assays, but Boyden assays showed reduced chemotaxis of immunomagnetic isolation-derived neutrophils. Finally, we confirmed that density-gradient purification induces artificial activation of neutrophils, evidenced by e.g. higher expression of CD66b, formyl peptide receptor 1 (FPR1) and CD35, and the appearance of a separate neutrophil population expressing surface molecules atypical for neutrophils (e.g. CXCR3, MHC-II and CD14). Based on these results, we recommend using immunomagnetic separation of neutrophils for studying neutrophil polarization, phagocytosis, ROS production, degranulation and NETosis, whereas for Boyden chemotaxis assays, the density-gradient purification is more suitable.